ONCOPLASTIC RESECTION OF MAMMAR Y GLAND WITH SIMULTANEOUS RECONSTRUCTION WITH LOCA TISSUES (USAGE OF LOWER GLANDULAR – TYPE SPAIR BY D. HAMMOND AND ST-INVERSE METHOD) - A. D. Zikiryakhodzhayev; E. A. Rasskazova; E. V. Тyshchenko (Исследования и практика в медицине)
The article presents oncoplastic resection with the usage of the lower glandular stems. The article described a radical resection of the breast, to restore the lost volume gland they mobilize the lower glandular stem, including deepithelized glandular-adipose flap with nipple-areola complex. They described the indications and contraindications to this surgery. They give two clinical examples with a description of the options of transactions. Also they perform surgery on conntralateral breast to achieve good cosmetic results and symmetry.